TEACHER'S STRATEGY IN CLASS MANAGEMENT OF STUDENTS IN CLASS IV OF SD NEGERI 018 RAMBAH SAMO - Rinja Efendi; Elvina; Marta, Eni; Rejeki (Cerdas Proklamator, 2023)
Quality education will produce quality human resources. Quality human resources must be the target of educational institutions to achieve it. The success or failure of achieving these goals will be seen from how the educational process is carried out by educational institutions. Teachers as educational staff are one of the determining factors for the success of educational goals, because teachers directly deal with students, to carry out their functions as educators. Teachers are educators who have the ability to class management. So that the teacher becomes the main factor in creating a conducive classroom atmosphere. Teachers need strategies to improve classroom management needed during learning. Class management provided by the teacher will make students excited because the classroom conditions remain conducive. The purpose of this research is to find out how the classroom teacher's strategy and the classroom teacher's constraints are in classroom management for students. This research method is used with the type of field research in the form of qualitative descriptive research. Data comes from primary and secondary sources which are collected through observation, interviews, and documentation. Data analysis techniques were carried out by going through four stages of data collection, data conventions, data presentation, and drawing conclusions. the validity of the data was tested for credibility, transferability, dependability and confirmability. The results of research conducted at SD Negeri 018 Rambah Samo found that teachers already have a strategy in class management in the form of organizing the classroom, setting class rules, distributing materials and tools, managing work/tasks, maintaining appropriate behavior. Based on the results of research at SD Negeri 018 Rambah Samo, it can be concluded that classroom management is by arranging classrooms, setting class rules, distributing materials and tools, managing work/tasks, maintaining appropriate behavior.